Hợp đồng tâm lý và giữ chân nhân viên: Vai trò trung gian của thương hiệu tuyển dụng, danh tiếng doanh nghiệp và sự hài lòng trong công việc - Đoàn Viết, Nhân; Phan Quốc, Tấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
Retaining employees in construction companies in Ho Chi Minh City has become increasingly difficult due to the recent economic crisis, resulting in weakened financial stability and workforce instability. This study investigates the relationship between psychological contracts and employee retention, focusing on the mediating roles of job satisfaction, employer brand, and corporate reputation. Using quantitative methods and SmartPLS software to analyze data from 427 employees, the hypotheses regarding the impact of psychological contracts on employee retention were tested and supported. The results also reveal gender differences in the relationship between job satisfaction and employee retention, and between psychological contracts and employer brand. Additionally, the findings indicate differences in employee retention based on age and marital status. Based on these findings, several implications for managers are proposed to enhance psychological contracts, employer branding, corporate reputation, and job satisfaction to contribute to employee retention in construction enterprises.